Ubiquitous computing and ambient intelligence : 11th International Conference, UCAmI 2017, Philadelphia, PA, USA, November 7-10, 2017, Proceedings /: 11th International Conference, UCAmI 2017, Philadelphia, PA, USA, November 7-10, 2017, Proceedings. (2017) - Unknown
No abstract available